(untitled) (Medico Legal Update, 2021)
Background: Children under five years of age suffer from anemia is a common medical problem worldwide. Iron deficiency anemia is the most prevalent in infants and has proven to be a public health issue. Many studies have been conducted on anemia among infants but the scope of the studies focused on anemia prevalence with less emphasis on anemia knowledge and parental practice. Objective: To explore the level of parental knowledge, attitude, and practice towards iron deficiency anemia. Method: A cross-sectional study in the first taken 150 children that attended to Children’s Counseling at Madinah General Hospital from these in the second case control study show only 30 children that effect with IDA and 30 children without IDA. Results: In this study, the prevalence of anemia in less than two years is 46.7%. knowledge answers near half study sample with their children previously diagnosed with IDA was 16 (53 %), the attitude of parents about IDA between two groups not there is a significant relationship and most answers of parents with their children previously diagnosed with IDA was between Fair 17 (57%) and Poor 11(36%), not there is a smaller study in this article to refuse or accepted. Practices show a significant association between (case with IDA) and (control without IDA) because (65% poor) practice About IDA in the case in other side control was (26%) poor only About IDA in the differential in practice refer more vulnerable to the effect of children to IDA. Conclusion: Anemia is prevalent in infants 24 months old with substantial differences in parents’ knowledge and practices.